Dosimetric feasibility of hypofractionation for SBRT treatment of lymph node oligometastases on the 1.5T MR-linac. (January 2021) - Winkel, Dennis; Werensteijn-Honingh, Anita M.; Eppinga, Wietse S.C.; Intven, Martijn P.W.; Hes, Jochem; Snoeren, Louk M.W.; Visser, Sanne A.; Bol, Gijsbert H.; Raaymakers, Bas W.; Jürgenliemk-Schulz, Ina M.; Kroon, Petra S.
Highlights: Lymph node oligometastases were treated using a 1.5T MR-linac with a 5x7 Gy scheme. Hypofractionated schedules were investigated based on dose criteria and quality. Plan quality of online adapted plans was compared. Hypofractionated radiotherapy for lymph node oligometastases on the 1.5T MR-linac is feasible. Abstract: Purpose: At our department, MR-guided stereotactic body radiation therapy (SBRT) using the 1.5T MR-linac system (Unity, Elekta AB, Stockholm, Sweden) has been initiated for patients with lymph node oligometastases. Superior soft tissue contrast and the possibility for online plan adaptation on the Unity may allow for hypofractionated treatment. The purpose of this study was to investigate the dosimetric feasibility and compare the plan quality of different hypofractionated schemes. Methods and materials: Data was used from 12 patients with single lymph node oligometastases (10 pelvic, 2 para-aortic), which were all treated on the Unity with a prescribed dose of 5x7 Gy to 95% of the PTV. Hypofractionation was investigated for 3x10 Gy and 1x20 Gy schemes (all 60 Gy BED α/β = 10). The pre-treatment plans were evaluated based on dose criteria and plan quality. If all criteria were met, the number of online adapted plans which also met all dose criteria was investigated. For pre-treatment plans meeting the criteria for all three fractionation schemes, the plan quality after online adaptation was compared using the four parameters described in the NRG-BR001 phase 1 trial. Results: Pre-treatment plans met all clinical criteria for the three different fractionation schemes in 10, 9 and 6 cases. 50/50, 45/45 17/30 of the corresponding online adapted plans met all criteria, respectively. Violations were primarily caused by surrounding organs at risk overlapping or adjacent to the PTV. The 1x20 Gy treatment plans were, in general, of lesser quality than the 5x7 Gy and 3x10 Gy plans. Conclusion: Hypofractionated radiotherapy for lymph node oligometastases on the 1.5T MR-linac is feasible based on dose criteria and plan quality metrics. The location of the target relative to critical structures should be considered in choosing the most suitable fractionation scheme. Especially for single fraction treatment, meeting all dose criteria in the pre-treatment situation does not guarantee that this also applies during online treatment.